Using Rough Set Theory to Find Minimal Log with Rule Generation - Alawneh, Tahani Nawaf E`layan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
The current research aims to enhance real-time analysis and speed of security algorithms by focusing on creating a minimal security log with the same efficiency as the original one through keeping core knowledge. Hence, manipulating this created minimal log with any security algorithm will surely enhance execution time and accordingly push towards real-time analysis. Rough set concepts are being used to reduce log size by using algorithms of the RoughSets package in R language, these algorithms guarantee to find a minimum log at least, and to find a minimal log at most depending on hardware resources available. Embedded knowledge is being extracted from minimum and minimal logs in the form of IF...THEN statements, and finally conclusions were discussed. Keywords: hate speech, text classification, classifier, classifier ensembles, stacking ensemble, text mining, genetic programming, pattern classification.

ÖZ: Mevcut araştırma, temel bilgileri koruyarak orijinali ile aynı verimliliğe sahip minimum bir güvenlik günlüğü oluşturmaya odaklanarak güvenlik algoritmalarının gerçek zamanlı analizini ve hızını artırmayı amaçlamaktadır. Bu nedenle, oluşturulan bu minimum günlüğü herhangi bir güvenlik algoritmasıyla manipüle etmek, yürütme süresini kesinlikle artıracak ve buna bağlı olarak gerçek zamanlı analize doğru itecektir. RoughSets paketinin algoritmalarını R dilinde kullanarak log boyutunu küçültmek için kaba küme konseptleri kullanılmaktadır, bu algoritmalar mevcut donanım kaynaklarına bağlı olarak en az minimum log, en fazla minimum log bulmayı garanti etmektedir. Gömülü bilgi, IF...THEN ifadeleri biçiminde minimum ve minimum günlüklerden çıkarılıyor ve son olarak sonuçlar tartışıldı. Anahtar Kelimeler: kaba küme teorisi; denklik sınıfları; daha düşük yaklaşım; üst yaklaşım; R dili.
Doctor of Philosophy in Applied Mathematics and Computer Science. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2022. Supervisor: Assist. Prof. Dr. Mehmet Ali Tut.
Keywords: Mathematics; Applied Mathematics and Computer Science; Information System Security; Computer network security; Computer security; Database searc hing; Hate speech; text classification; classifier; classifier ensembles; stacking ensemble; text mining; genetic programming; pattern classification